Ellen Lupton - Padovani, Stephania (InfoDesign, 2007)
<img title="id_v4_n1_2007_55_56_padovani_291" src="http://www.infodesign.org.br/revista/public/site/images/fnunes/id_v4_n1_2007_55_56_padovani_291.jpg" alt="id_v4_n1_2007_55_56_padovani_291" width="199" height="291" /> Ellen Lupton is a writer, curator, and graphic designer. She is director of the Graphic Design MFA program at Maryland Institute College of Art (MICA) in Baltimore, where she also serves as director of the Center for Design Thinking. As curator of contemporary design at Cooper-Hewitt, National Design Museum since 1992, she has produced numerous exhibitions and books. She recently has focused on bringing design awareness to broader audiences. Her book Thinking with Type (2004) is a basic guide to typography directed at everyone who works with words. D.I.Y.: Design It Yourself (2006), co-authored with her graduate students at MICA, explains design processes to a general audience. Her newest project, D.I.Y. Kids (October 2007), co-authored with Julia Lupton, is a design book for children illustrated with kids’ art. Lupton is a 2007 recipient of the AIGA Gold Medal, one of the highest honors given to a graphic designer or design educator in the U.S.